Rare Breast Malignancies - Yildirim, Nilgun; Aldemir, Mehmet Naci; Simsek, Melih; Bilici, Mehmet; Tekin, Salim Basol (Yerkure Tanitim & Yayincilik Hizmetleri A S, 2019)
Objective: Invasive breast cancer is a heterogeneous disease group that has different biological and pathological features, and characterized with different clinical behavior, treatment results, and consequences. The rarity of most specific neoplasies does not allow large or randomized studies to determine optimal treatment. With this study, we aimed to evaluate the clinical and pathological features and treatment options and results of rare breast carcinoma patients that followed and treated in our clinic. Methods: Files of 1280 breast cancer patients admitted to our center between years 2000 and 2016 were evaluated. From these patients, who have rare breast carcinoma subtypes were included and patients with pathological diagnosis of invasive ductal carcinoma and invasive lobular carcinoma were excluded. Seventy-three patients that included in the study were analyzed retrospectively in terms of age, menopausal status, family history, tumor-lymph node-metastasis stage, histological grade, hormone receptor level, human epidermal growth factor receptor2 expression, operation type and overall survival (OS). Results: Eight histological subtypes of breast tumors were evaluated. Significant difference wasn't found between groups in terms of mean age of the patients. In terms of histological subtypes, the most eldest patients were in papillary group, the youngest patients were in tubular group. The mean tumor diameter was also significantly different between groups (p=0.02). The mean age of the patients diagnosed with tubular and mucinous type breast carcinomas were younger than the one reported in literature and the mean tumor diameter was also larger in these tumors. Ratio of patients diagnosed at advanced stages was high (43%). While mucinous and tubular carcinomas were the histological subtypes with the best prognosis, the shortest OS was in primary breast sarcoma and neuroendocrine carcinoma group. Conclusion: Rare breast cancers are a heterogeneous malignity group with different behavior and prognosis. Our results, except some cases, were generally concordant with the data obtained from other studies. These exceptions may be related to race, regional factors, different pathological evaluation, and environmental factors. Nevertheless, comprehensive clinical studies are required because of the rare occurrence these tumors.
Nadir Meme Tümörleri
Keywords: Breast carcinoma; histological types; rare breast tumors